Consideration of carbon nanotube-based nanofluid in thermal transfer - Mare, Thierry (Penerbit UTM Press, 2016)
In the current trend towards demand for effective heat removal of high density heat flux, research into nanofluids have escalated due to the rise in thermal conductivity associated with the coolants. Are nanofluids a solution for a better thermal management? Does the application of nanofluids as coolants have limitations? This article presents a review of the thermophysical properties of carbon nanotube-water nanofluids, in particular the desired properties of low viscosity and high thermal conductivity. The effects of the concentration, temperature, aspect ratio, and surfactant on the thermal conductivity and viscosity of carbon nanotube nanofluid have been studied experimentally. These effects are thendiscussed for evaluation of the applicability of carbon nanotube-based nanofluidas a coolant for heat removal purposes.